Pengaruh Boards Diversity (CEO Wanita, CFO Wanita, Proporsi Dewan Komisaris Wanita, Proporsi Komite Audit Wanita) Terhadap Pelanggaran Aturan Laporan Keuangan - Kholida Atiyatul Maula; Arif Rakhman (Accounthink, 2018)
The focus of this study was on female CEOs, female CFOs, the proportion of female commissioners, and the proportion of female audit committees. This study measures how gender-based board diversity through the presence of female executives exerts an influence on the violation of financial reporting rules conducted by public companies in Indonesia. This study uses the assumption that gender differences will affect a person's behavior. Female and male will have different considerations and actions, for example in terms of cognitive functioning, decision making, and conservatism that may have important implications in the quality of financial reporting. Populations in this study are all non-financial companies that violate financial rules according to Otoritas Jasa Keuangan (OJK). The results of the study explain that female CEO variables and proportion of female board of directors negatively affect the level of financial reporting violations, while female CFOs and female audit committees have no influence on the level of violation of financial statement rules.